Three new species of Barringtonia (Lecythidaceae) from Myanmar and Vietnam - Thammarong, Woranart; Chantaranothai, Pranom; Pornpongrungrueng, Pimwadee (Phytotaxa, 2017)
Three new species of Barringtonia (Lecythidaceae) are herein described, B. laxiflora Thammar., Pornp. & Chantar. and B. tomentosa Thammar., Pornp. & Chantar. from Vietnam, and B. parkinsonii Thammar., Pornp. & Chantar. from Myanmar. Distribution maps and illustrations are also presented.